2022
DOI: 10.1007/s11858-022-01433-8
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of exponential growth as a rich learning environment for mathematics classrooms

Abstract: Mathematical concepts are regularly used in media reports concerning the Covid-19 pandemic. These include growth models, which attempt to explain or predict the effectiveness of interventions and developments, as well as the reproductive factor. Our contribution has the aim of showing that basic mental models about exponential growth are important for understanding media reports of Covid-19. Furthermore, we highlight how the coronavirus pandemic can be used as a context in mathematics classrooms to help studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…In this way, technology can enhance connections between various types of mathematical knowledge (Geiger, 2011). Overall, studies reported that technology offered plenty of opportunities for students and confirmed that technology can be successfully applied at different stages of the modelling cycle, including simplification, mathematization, making connections, evaluation, interpretation, and validation (Siller and Greefrath, 2010;Geiger, 2011;Daher and Shahbari, 2015). In line with our results, Molina-Toro et al (2019) found that studies on modelling used digital tools to visualize the representation of data, make complicated calculations, develop or validate mathematical models and simulate phenomena.…”
Section: Advantages Of Using Digital Technologies In Mathematical Mod...mentioning
confidence: 79%
See 3 more Smart Citations
“…In this way, technology can enhance connections between various types of mathematical knowledge (Geiger, 2011). Overall, studies reported that technology offered plenty of opportunities for students and confirmed that technology can be successfully applied at different stages of the modelling cycle, including simplification, mathematization, making connections, evaluation, interpretation, and validation (Siller and Greefrath, 2010;Geiger, 2011;Daher and Shahbari, 2015). In line with our results, Molina-Toro et al (2019) found that studies on modelling used digital tools to visualize the representation of data, make complicated calculations, develop or validate mathematical models and simulate phenomena.…”
Section: Advantages Of Using Digital Technologies In Mathematical Mod...mentioning
confidence: 79%
“…The black box issue frequently arises when the creator and user are not the same person (Greubel and Siller, 2022). Concerning this challenge, research has shown that the difficulties frequently encountered in solving modelling problems in digital group work appear to be a direct result of the automatic calculation provided by technological tools (Siller et al, 2022). Studies highlighted that for students who avoided necessary validity checks, it might be easy to blindly trust digital technologies, get lost in the modelling process, and disengage from the solution to the modelling problem.…”
Section: Challenges To the Use Of Digital Technologies In Mathematica...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is also quite a strong focus on developing a public understanding of mathematics that is used by the media to explain and predict trends in the pandemic and other global phenomena. In their study Siller et al ( 2022 ) addressed the way the media present data on the pandemic, referring to growth models, which attempt to explain or predict the effectiveness of interventions and developments, as well as the reproductive factor. Since these reports sometimes appeared contradictory or even false to students, they showed that basic mental models about exponential growth are important for understanding media reports of COVID-19.…”
Section: The Changing Classroom—impact On Mathematics Educationmentioning
confidence: 99%